Kimchi and Other Widely Consumed Traditional Fermented Foods of Korea: A Review - Patra, Jayanta Kumar; Das, Gitishree; Paramithiotis, Spiros; Shin, Han-Seung (Frontiers in Microbiology, 2016)
Different types of fermented foods such as chongkukjang, doenjang, ganjang, gochujang and kimchi are plentifully available and widely consumed in north eastern Asian countries including Korea. Among them, kimchi is one of the most popular Korean traditional food. It is prepared by fermenting the baechu cabbage together with other vegetables and lactic acid bacteria with functional potential. Many types of ingredients are added to kimchi to enhance its taste, flavor, nutritional value, texture etc. A number of bacteria are involved in the fermentation of kimchi, but lactic acid bacteria are the dominant species in the fermentation process. The addition of other sub ingredients and formation of different by-products during fermentation eventually leads to eradication of putrefactive and pathogenic bacteria, and also increase the functionalities, nutritional and nutraceutical potential of kimchi. Kimchi possesses anti-inflammatory, antibacterial, antioxidant, anticancer, antiobesity, probiotic properties, cholesterol reduction, and antiaging properties. In the present review an attempt has been made to review the different types of fermented foods found in the Korean peninsula with detailed scientific research regarding preparation, processing, structure of the microecosystem and health benefits of kimchi.